Surgical revascularization: an innovative approach to the treatment of talar osteonecrosis dissecans stages II and III - Struckmann, Victoria; Harhaus-Wähner, Leila; Recum, Jan von; Kneser, Ulrich; Kremer, Thomas (The journal of foot and ankle surgery, 2017)
Talar osteonecrosis dissecans is caused by osseous malperfusion, leading to destruction of the talar bone. The current reference standard for advanced stages lacking arthrosis is core decompression, followed by autologous cancellous bone grafting. However, talar revascularization has not been observed in a subset of patients after this procedure. Microsurgical vascularized bone grafting can improve outcomes by the induction of angiogenesis. We present the 1-year follow-up data from 3 patients with talar osteonecrosis dissecans, who had undergone free vascularized medial femoral condyle autotransplantation. The patients were evaluated preoperatively and 3, 6, and 12 months postoperatively. The active range of motion, pain (visual analog scale [VAS]), and American Orthopaedic Foot and Ankle Society ankle-hindfoot scale, and lower extremity functional scale were used. Osteonecrosis dissecans stage II was seen in patient 1 (aged 27 years) and stage III in patients 2 (aged 18 years) and 3 (aged 41 years). Preoperative pain of the ankle was recorded as VAS score of 3 by patients 1 and 2 and VAS score of 6 by patient 3. At 12 months postoperatively, patients 1 and 2 recorded a VAS score of 2 and patient 3, a VAS score of 0. All patients showed improvement in the lower extremity functional scale and American Orthopaedic Foot and Ankle Society scale scores. After 6 and 12 months, magnetic resonance imaging showed a well-vascularized femoral condyle incorporated into the talus in all the patients. Autotransplantation of vascularized bone grafts from the medial femoral condyle is a promising technique for surgical revascularization of talar osteonecrosis dissecans stage II and III.
Available online 16 April 2016
Gesehen am 20.08.2020